1998
DOI: 10.1002/14651858.cd000495
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic ultrasound for postpartum perineal pain and dyspareunia

Abstract: Analysis 1.11. Comparison 1 Ultrasound versus placebo for acute perineal pain, Outcome 11 Haemorrhoids post-treatment...... Analysis 1.12. Comparison 1 Ultrasound versus placebo for acute perineal pain, Outcome 12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 19 publications
0
18
0
2
Order By: Relevance
“…The main metabolite of hydromorphone is hydromorphone-3-glucuronide (H3G), a structural analogue of morphine-3-glucuronide (M3G). Like M3G (see below) H3G is dependent on the kidney for excretion, has no analgesic action and can lead to dosedependent neurotoxic effects (Smith, 2000;Wright et al, 2001;Murray & Hagen, 2005).…”
Section: Chaptermentioning
confidence: 99%
“…The main metabolite of hydromorphone is hydromorphone-3-glucuronide (H3G), a structural analogue of morphine-3-glucuronide (M3G). Like M3G (see below) H3G is dependent on the kidney for excretion, has no analgesic action and can lead to dosedependent neurotoxic effects (Smith, 2000;Wright et al, 2001;Murray & Hagen, 2005).…”
Section: Chaptermentioning
confidence: 99%
“…A lot of studies had focused on the dyspareunia in immediate postnatal perineal pain and found the effects of ultrasound therapy, pulsed electromagnetic therapy and found its effect on quality of life and pain [15][16][17][18][19]. However, only very few studies had found the effect of ultrasound therapy over the complicated episiotomy scar and no studies had compared scar mobilization and ultrasound over superficial dyspareunia.…”
Section: Discussionmentioning
confidence: 99%
“…Although improvement in perineal pain has been reported with ultrasound, there is insufficient evidence to fully evaluate efficacy (Hay-Smith, 2000 Level I).…”
Section: Non-pharmacological Treatmentsmentioning
confidence: 99%